THE AMBITION OF THE MAJOR CHARACTER IN JUSTIN CHADWICK'S THE OTHER BOLEYN GIRL MOVIE (2008): A BEHAVIORIST PERSPECTIVE - HANDAYANI, CINDY MUTI (2011)
The object of this research is the movie entitled The Other Boleyn Girl, by Justin Chadwick. The study investigates how the ambition change behavior of the major character in Justin Chadwick's The Other Boleyn Girl specifically viewed from behaviorist perspective. The research paper belongs to qualitative research. The object of the study is Anne Boleyn in The Other Boleyn Girl movie. In this method, the writer uses two data sources. The primary data source is the The Other Boleyn Girl movie itself, meanwhile the secondary one includes references and materials related to the study picking up from the books or internet. The methods used for collecting data are library research and documentation. The technique of data analysis is descriptive analysis. The result of the study reveals the life of Anne Boleyn who change her behavior beacuse her big ambition. The Other Boleyn Girl represents Justin Chadwick's response to the role of ambition in changing and shaping someone's behavior.